Research and Progress on the Association of Porphyromonas gingivalis with Lung Cancer - Yuanyuan YIN; Jie ZHANG; Qiang GUO; Cheng SHEN (Chinese Journal of Lung Cancer, 2024)
Porphyromonas gingivalis is a key pathogenic microorganism that triggers periodontitis. It is closely associated with oral diseases such as chronic periodontitis and recently found to have a significant correlation with the occurrence, progression, and prognosis of cancer. As the leading malignant tumor in terms of both incidence and mortality worldwide, lung cancer has always been a focus and hotspot of research. The causes of lung cancer are complex and involve multiple factors, including smoking, occupational factors, air pollution, ionizing radiation, diet and nutrition, genetic factors, etc. Researchers have also begun to pay attention to the relationship between oral microbiota and overall health, especially the link with lung cancer. The article summarizes the latest advancements in research on Porphyromonas gingivalis in lung cancer, primarily encompassing etiology and pathogenic mechanisms, and explores its potential as a therapeutic target for lung cancer, aiming to provide new insights and directions for lung cancer prevention and treatment strategies.